2021
DOI: 10.1007/s10865-021-00211-3
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-specific friend support in emerging adults with type 1 diabetes: Does satisfaction with support matter?

Abstract: Youth with type 1 diabetes (T1D) must adhere to a complex treatment regimen to prevent health complications. Friends may provide diabetes-specific support to help youth manage diabetes, but evidence on whether youth benefit from diabetes-specific friend support is inconclusive. The present study first investigated whether satisfaction with friend support was linked to psychological distress and diabetes management. Second, it was investigated whether self-esteem mediated these relations. To this end, 324 Dutch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…A chronic illness such as T1DM requires a considerable variety of therapeutic behaviors, such as counting carbohydrate, checking blood glucose multiple times a day, and administering insulin in response to blood glucose levels [ 42 ]. Some authors refer to treatment as a difficult, multi-step, complex, intensive, demanding, and highly visible regimen to others, which requires the adoption of a diet that keeps adequate glucose levels and the maintenance of physical activity [ 43 , 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…A chronic illness such as T1DM requires a considerable variety of therapeutic behaviors, such as counting carbohydrate, checking blood glucose multiple times a day, and administering insulin in response to blood glucose levels [ 42 ]. Some authors refer to treatment as a difficult, multi-step, complex, intensive, demanding, and highly visible regimen to others, which requires the adoption of a diet that keeps adequate glucose levels and the maintenance of physical activity [ 43 , 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Participants rate behaviors on frequency of occurrence and satisfaction. Utilizing the DSSQ-Fr, one study showed peer support was related to more diabetes distress-unless youth were satisfied with the support received (Raymaekers et al, 2021), one study showed peer support was unrelated to self-care or glycemic stability (Doe, 2018), and one study found the relation of diabetes distress to poor glycemic stability was stronger for those with high peer support (Hains et al, 2007). These findings are striking because no study found clear links of diabetes peer support to healthy functioning.…”
mentioning
confidence: 99%